The Impact of Young Women Imagery on Advertisement Towards Purchase Intention of Pocari Sweat - Muhammad, Irham Alifa; Windasari, Nila Armelia (Journal of Business and Management, 2021)
Advertisement has been important to share companies’ values and perceptions. Though the portrayal of women in advertising is often shown with common fundamental characteristics. Indonesia’s relatively conservative views on gender, and Pocari Sweat’s often use of women as the dominant character, there is the incentive for Pocari Sweat to re-evaluate the effectiveness of their ads. This study aims to understand how women-dominated advertisement could influence male and female customer’s purchase intention of Pocari Sweat. To achieve these objectives this research incorporates the Stimulus-organism-response model (SOR) as a base framework. Questionnaires are distributed through an online form and received 168 responses from respondents aged 14-50 years old living in Indonesia. Through descriptive analysis and PLS-SEM, this research showed that customers perceive the advertisement to be well made. Males are not affected by the ads as much as females emotionally, and self-congruency for female respondents will have an effect to their purchase intention. This research could provide insights to marketers to be aware of which factors that significantly affect customer purchase intention of male and females. Moreover, demonstrate the significance of self-congruence as a factor to test the effect on purchase intention for low-involvement beverage products such as Pocari Sweat.Keywords: Advertisement, Purchase Intention, Women Imagery, Perception towards Women, Self-congruence